Vertebral Osteomyelitis and Spinal Epidural Abscess: An Evidence-based Review. Issue 6 (July 2015) - Boody, Barrett S.; Jenkins, Tyler J.; Maslak, Joseph; Hsu, Wellington K.; Patel, Alpesh A.
Abstract : Spinal infections have historically been associated with significant morbidity and mortality. Current treatment protocols have improved patient outcomes through prompt and accurate infection identification, medical treatment, and surgical interventions. Medical and surgical management, however, remains controversial because of a paucity of high-level evidence to guide decision making. Despite this, an awareness of presenting symptoms, pertinent risk factors, and common imaging findings are critical for treating spine infections. The purpose of this article is to review the recent literature and present the latest evidence-based recommendations for the most commonly encountered primary spinal infections: vertebral osteomyelitis and epidural abscess.